Research on Design Method Based on Hardware Encryption and Two-way ID Authentication for Security Mobile Hard Disk - Huanchun Yang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The design Method of the " Security Mobile Hard Disk Based on Hardware Encryption and Two-way ID Authentication" adopts the smart card-based technology of two way ID authentication, thus enables higher authentication strength than ordinary password authentication and USB-KEY one way certification; adoption of dedicated hardware encryption chip on encrypting the hard disk data enhances the encryption speed; since this encryption is a hardware level encryption, it is completely transparent to users, and do not rely on the operating system or other applications, with almost no impact on system performance; that the key of the encryption system will be loaded before the system initialization (system boot) prevents malicious code attacks from hard drive, and even when the mobile hard disk was stolen, the thief cannot read out any encrypted data from it  on any other computer as long as the thief has no access to the encryption key. Therefore, this "encrypted mobile hard disk" is more secure with better reading and writing performance, and thus can effectively protect Important and sensitive data on the mobile hard disk. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4995